A study on the relationship between unemployment, GDP growth and population with the rising crime rates in Malaysia / Effie Laurence Edin - Edin, Effie Laurence (2014)
This study is designed to investigate the relationship between unemployment, GDP growth and Population with the rising crime rates in Malaysia. The study covers the period for 1982-2011. For this study, Statistical Package Social Science (SPSS) is used to analyze all the data collected. The estimated result assume that unemployment, GDP growth and population are positive related to crime rate and have significant relationship. However, GDP growth is not significant while unemployment is negative related with crime rates.